ENZYMES OF TUBERCULOUS TISSUE - Opie, Eugene L. (The Rockefeller University Press, 1908)
Epithelioid cells which form the chief element of tuberculous tissue contain an enzyme which causes active digestion of proteid in an approximately neutral or in a weakly acid medium, but is inactive in the presence of weak alkali. This enzyme resembles that which occurs in the large mononuclear cells of an inflammatory exudate and is more active than the similar enzyme of parenchymatons organs such as the liver. The enzyme which digests in the presence of acid exhibits greatest activity at a time when caseation is beginning. With advance of caseation its activity diminishes so that tissue which has undergone almost complete caseation exhibits trivial evidence of the presence of enzyme. It is probable that complete caseation is followed by total disappearance of enzymes. Tuberculous tissue contains an enzyme capable of digesting proteid in the presence of alkali (leucoprotease) only during the early stages of its development. This enzyme, present at a time when the tissue contains numerous polynuclear leucocytes, quickly disappears so that when enzyme digesting in acid is still active, leucoprotease has disappeared. The serum of a tuberculous pleural exudate obtained by intrapleural inoculation with tubercle bacilli causes slight inhibition of the mixture of enzymes contained in tuberculous tissue shortly after inoculation. The serum of blood causes complete inhibition of the enzymes contained in the same tuberculous tissue. Analysis of this difference indicates that the exuded tuberculous serum, like the serum of the blood, inhibits proteolysis caused by leucoprotease, but fails to inhibit digestion caused by an enzyme acting in the presence of acid. In testing this property of the exuded tuberculous serum lymphatic gland has been used because suitable tuberculous tissue has not been available. The serum of the tuberculous pleural exudate produced experimentally not only fails to exert the anti-enzymotic power which is exhibited by the serum of the blood, but is itself capable of causing active digestion of coagulated proteid. Normal blood serum does not digest proteid and the serum of a sterile inflammatory exudate obtained by injection of turpentine into the pleural cavity has caused very little digestion. The tests which have been made indicate that loss of anti-enzymotic power and ability to cause proteolysis increase with the age of the exudate. The foregoing facts offer suggestions which may serve to explain in part the nature of the tubercle and the changes which occur within it. The so-called epithelioid cells of the tubercle resemble the large mononuclear phagocytes of inflammatory exudates and both contain an enzyme of the same character. It is not improbable that caseation which, like autolysis, is accompanied by disappearance of nuclei is in part dependent upon the presence in the cells of this active proteolytic enzyme which is for a time held in check. Injury to cells by products of the tubercle bacillus or partial anæmia, the result of imperfect vascularization of the tuberculous tissue, may have a part in rendering these cells susceptible to self-digestion. Changes which have been observed in serum of the tuberculous exudate show that the anti-enzymotic property of the normal blood may be absent in the exudate of a tuberculous lesion. This loss of anti-enzymotic action, perhaps referable to changes caused by products of the tubercle bacillus, may favor self-digestion of the enzyme-containing cells and diffusion of their enzyme.